Relationship between inflation and interest rate in China - xie, jiejin (2009)
Abstract How to control the inflation rate to a target level is an important research topic in economics. Particularly, since July 21st 2005, Chinese exchange rate regime reform happened, which made (Renmibi) RMB value depreciated and caused inflation pressure. In addition interest rate is an important instrument for government to control inflation, it is very important to analyze the relationship between inflation rate and interest rate. The purpose of this paper is to estimate whether there is a significant relationship between inflation (or expected inflation) and interest rate. If the relationship exists, is it positive or negative? Simultaneously, this paper investigates whether the Fisher effect exists in China. Secondary research and quantitative measure are conducted to identify the relationship between inflation (or expected inflation) and interest. Autoregressive model, Augmented Dickey-Fuller test and Co-integration test will be applied. The findings of this paper indicate that official interest rate have significant positive relationship with inflation and expected inflation, while market interest rate have weak positive relationship with inflation and expected inflation. However the one-to-one Fisher coefficient dose not establish in China.